2015
DOI: 10.1111/1440-1681.12377
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acetyltransferases cyclic adenosine monophosphate response element‐binding binding protein and acetyltransferase p300 attenuate transcriptional activity of the mineralocorticoid receptor through its acetylation

Abstract: Acetylation of the mineralocorticoid receptor (MR) by inhibition of lysine deacetylases attenuates MR's transcriptional activity. However, the specific lysine acetyltransferases that are responsible for acetylation of the MR remain unknown. We hypothesized that the acetyltransferases cyclic adenosine monophosphate response element-binding binding protein (CBP) and acetyltransferase p300 (p300) attenuate transcriptional activity of the MR through its acetylation. Expression of MR target genes was measured by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since nonhistone acetylation was first identified, increasingly more functions for acetylation have been found to act on various life processes, including DNA damage response and autophagy (Botrugno et al, 2012;Zhong et al, 2017;Yasuda et al, 2018), genomic stability (Billon et al, 2017;Fournier and Tora, 2017), transcriptional activity (Seo et al, 2015), protein degradation (Liu et al, 2013;Wei et al, 2018) and lysosomal function (Zhang et al, 2018). Previous studies have shown that acetylation could compete with ubiquitination at the same lysine residue, thus blocking the ubiquitin-mediated proteasomal degradation pathway to improve the protein stability, which is involved in cell cycle regulation (Lahusen et al, 2018), tumour suppression and progression (Wan et al, 2015;Choi et al, 2017), bacterial virulence (Sang et al, 2017) and signal transduction (Garcia-Aguilar et al, 2016;Beckwith et al, 2018;Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…ApoLp-III, as an RNA binding protein, sends out an alarm signal by binding to a specific RNA during bacterial invasion (Park et al, 2005). ApoLp-III is also involved in many insect immune responses, such as those of Heliothis virescens (Gupta et al, 2010), Hyphantria cunea (Contreras et al, 2013), Anopheles gambiae (Lourenco et al, 2009) and Tribolium castaneum Herbst (Seo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of class 1 HDACs promoted MR acetylation, attenuated recruitment of MR and RNA polymerase II to the promoters of target genes and reduced expression of MR target genes [100] manifesting as decreased transcriptional activity [102]. CBP or p300 increased MR acetylation, decreased recruitment of MR and Pol II to specific hormone response elements and decreased expression of MR target genes in HEK cells [102,103] without affecting sub‐cellular localization.…”
Section: Acetylation Of Nuclear Receptors Governs Hormone Signallingmentioning
confidence: 99%
“…Surprisingly, K677 acetylation did not affect MR nuclear translocation [36], even though this residue is located in NL1. This study and subsequent work by the same group identified CREB-binding protein (CRE)/p300 as the acetylase and HDAC3 as the deacetylase responsible for modifying K677 [36,73] (Figure 2). The molecular basis for the lack of MR binding to target promoters when acetylated at residue K677, which is away from the DBD, is unknown.…”
Section: Post-translational Modifications Controlling Mr Activation Amentioning
confidence: 75%